Comparison of novel bioactive, bioceramic materials in vital pulp therapy in deciduous teeth – a clinical in vivo study - Acharya, Sonu; Gurunathan, Deepa (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. The use of modern bioceramic materials has enhanced the predictability of vital pulp therapy. This study aimed to assess the clinical success of Biodentine, modified NeoPutty mineral trioxide aggregate (MTA), and calcium hydroxide Ca(OH)2 as pulp capping materials for indirect pulp capping in carious primary teeth. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. Indirect pulp treatment (IPT) was performed on 36 deciduous molars in 36 patients who were presented with deep carious lesions. The teeth were randomly assigned to three groups: Biodentine (12 teeth), modified NeoPuttyMTA (12 teeth), and Ca(OH)2 (12 teeth). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. A statistical analysis was conducted using SPSS software version 21.0. Pearson’s Chi-square test was employed to compare success and failure rates among Biodentine, modified Neoputty MTA, and Ca(OH)2 at three different time intervals (30, 90, and 180 days) and overall success and failure rates regardless of the time intervals. In the statistical analysis, different pulp capping materials yielded varying success rates. The modified NeoPutty MTA group demonstrated a success rate of 91.67%, the Biodentine group 83.33%, and the Ca(OH)2 group 58.33% after 6 months. However, these differences were not statistically significant. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. IPT with calcium silicate-based materials, such as Biodentine and modified NeoPutty MTA, showed superior results when compared to the use of calcium hydroxide Ca(OH)2. Although differences in success rates were observed among the materials, they did not reach statistical significance.